2015
DOI: 10.1007/s12028-015-0206-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propofol on Excitatory and Inhibitory Amino Acid Neurotransmitter Balance in Rats with Neurogenic Pulmonary Edema Induced by Subarachnoid Hemorrhage

Abstract: The current findings suggest that propofol improves NPE likely via IAA accumulation and the regulation of EAA and IAA balance, which may represent an effective treatment for NPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The most crucial cytokines in brain ischemic inflammatory response are IL-1, TNF-α, IL-6, IL-10, and transforming growth factor-β (TGF-β). In CIRI, excessive pro-inflammatory cytokines such as IL-6 and TNF-α are released and they suppress the production of anti-inflammatory cytokines such as IL-10, thus aggravating brain injury (Zhang et al, 2016). Reportedly, FPA represses IL-1β and TNF-α levels in a rat model of CIRI (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The most crucial cytokines in brain ischemic inflammatory response are IL-1, TNF-α, IL-6, IL-10, and transforming growth factor-β (TGF-β). In CIRI, excessive pro-inflammatory cytokines such as IL-6 and TNF-α are released and they suppress the production of anti-inflammatory cytokines such as IL-10, thus aggravating brain injury (Zhang et al, 2016). Reportedly, FPA represses IL-1β and TNF-α levels in a rat model of CIRI (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitters such as glutamate, norepinephrine (NE) (a marker of sympathetic activity), and gamma-aminobutyric acid (GABA) in the PVN are known to be involved in the pathogenesis of hypertension 11 12 . Glutamate and NE in the PVN are the neurotransmitters that excite the sympathetic outflow 13 , and GABA in the PVN is an important neurotransmitter that inhibits sympathetic activity 14 . Evidences showed that NE and GABA in the PVN contribute to the pathogenesis of hypertension 15 16 17 , Moreover, the hypertensive responses are due to increases of excitatory adrenergic and glutamatergic activities and a decrease of GABAergic activity in the PVN 18 .…”
mentioning
confidence: 99%
“…Our findings demonstrated that propofol increased GABA concentration, consistent with the view that general anesthesia inhibits excitatory synaptic transmission and enhances inhibitory synaptic transmission ( Wang et al, 2016 ; Yang et al, 2019 ). Notably, our study also showed that the concentrations of DA, Glu, NE, and ACh increased under propofol anesthesia, challenging prevailing perspectives ( Gamou et al, 2010 ; Shirasaka et al, 2011 ; Zhang et al, 2016 ). To unravel this unexpected phenomenon, we explored previous studies highlighting the potential of propofol to amplify neurotransmitter levels by inhibiting reuptake mechanisms ( Pain et al, 2002 ; Zhao & Sun, 2008 ; Zhu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 51%